PROJECT-BASED INTEGRATED LEARNING IN IMPROVING 21ST CENTURY INTERPERSONAL LANGUAGE COMMUNICATION SKILLS - ahmad fuadin; Firman - Aziz; Diena San Fauziya; Arjulayana - arjulayana (Universitas Muhammadiyah Tangerang, 2023)
The golden generation is the hope for improvement and acceleration of the rate of growth and development of the Indonesian nation during the one hundred years of independence. The golden generation must be prepared on all fronts. Education is one of the pillars of the formation of the golden generation. This study aims to analyze project-based integrated learning in improving 21st century interpersonal linguistic communication skills. Integrated learning can be realized through project synergies with four compulsory curriculum subjects, namely Religious Education, Pancasila Education, Citizenship Education, and Indonesian Language Education. This study used a descriptive qualitative method. The research instrument uses data from student learning assignments. The research was conducted for one semester with English Education students Batch 2022 who contracted the Indonesian Language Education General Course (MKU-PBI). The results of the research show that integrated learning can be done by: 1) synergizing theoretical and practical concepts that become learning orientation, 2) applying character values through the formation of 5C (critical thinking, creativity and innovation, communication skill, collaboration, and confidence), and 3) implementing interpersonal linguistic communication values. Thus, this research can be carried out in the future by involving many study programs or many groups.